Mengatasi Ketimpangan Pembangunan antara Wilayah Barat dan Timur Indonesia: Tantangan dan Solusi Ekonomi - Haryono, Dandan; Ramlah, St (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
Equitable development between the Western and Eastern regions of Indonesia is one of the major challenges in achieving national welfare. The significant development gap between these regions is caused by various factors such as centralized policies, limited infrastructure, and low human resource (HR) quality in Eastern Indonesia. The Western region, particularly Java, is more advanced in many sectors, while the Eastern region, rich in natural resources, is still lagging behind in access to education, health, and infrastructure. Several policies have been implemented by the government to reduce this gap, including the Special Allocation Fund (DAK) and the Regional Autonomy program, but the results remain limited. Therefore, solutions to reduce this gap include optimizing the potential of natural resources in Eastern Indonesia, equitable infrastructure development, and empowering the private sector to invest in the Eastern region. Developing the tourism sector, resource-based industries, and improving HR quality in Eastern Indonesia are also important steps to achieving more equitable development. With the right approach, development disparities can be reduced, enabling Indonesia to achieve inclusive and just development.